Enclosing classical polyoxometallates in silver nanoclusters. Issue 22 (29th May 2019) - Wang, Zhi; Sun, Yi-Ming; Qu, Qing-Ping; Liang, Yu-Xin; Wang, Xing-Po; Liu, Qing-Yun; Kurmoo, Mohamedally; Su, Hai-Feng; Tung, Chen-Ho; Sun, Di
Abstract : Two classic Polyoxometallates, Lindqvist-Mo6 O19 2− and V10 O28 6−, were encapsulated by three novel silver-thiolate clusters, [(V10 O28 )@Ag44 ] (SD/Ag44a ), [(V10 O28 )@Ag46 ] (SD/Ag46 ), and [(Mo6 O19 )@Ag44 ] (SD/Ag44b ). Abstract : Due to the elusive nature of polyoxometallates (POMs) in the assembly of silver clusters, POMs trapped by silver clusters are usually different from the pristine form, which surely increases the novelty of the assembly results but makes the final structure predictability challenging. Herein, three novel high-nuclearity silver-thiolate clusters trapping two kinds of classical POMs, Lindqvist-Mo6 O19 2− and V10 O28 6−, are reported. They are identified to be [(V10 O28 )@Ag44 ] (SD/Ag44a ), [(V10 O28 )@Ag46 ] (SD/Ag46 ), and [(Mo6 O19 )@Ag44 ] (SD/Ag44b ) clusters, which are further extended to 1D chain, 2Dsql layer, and 3Dpcu framework, respectively. Of note, SD/Ag44b contains a regular cubic Mo6 O19 core sealed by an Ag44 (EtS)24 shell in a pseudo-sodalite unit and six SCl4 planar squares connecting the respective adjacent silver tetragonal faces. This structure is a novel zeolite closely related to the natural alumino-silicate 'sodalite' but exceptionally made of core–shell silver clusters. Moreover, the Oh symmetric Mo6 O19 2− templates an Oh symmetric Ag44 cluster inSD/Ag44b, realizing authentic symmetry delivery from guest to host in this system. This is a rare silver cluster family with classical POMs encapsulated.